OA-oriented Practical Training Courses for English Education Majors in the Context of New Liberal Arts Reform Research - Siqin, gaowa (Pacific International Journal, 2025)
This study investigates the reform of practical training courses for English education majors under the New Liberal Arts initiative, guided by the Production-Oriented Approach (POA). It identifies existing problems such as singular teaching modes, insufficient practical experience, and inadequate teacher training. Through the integration of POA’s three-phase framework—Motivating, Enabling, and Assessing—the research proposes a student-centered restructuring of practical training. Using the English Teaching Theory and Practice course as a case study, the paper demonstrates how POA enhances teaching competency through task-based, collaborative, and evaluative learning. Findings indicate that POA-driven reforms significantly improve students’ practical teaching skills, critical thinking, and readiness for real-world educational environments. This study offers a replicable model for practical curriculum innovation in English teacher education.